maths
posted by ryan j .
help find the general solution of the following first order differential equation.
t*(dy/dt) = (y/t) + ((exp(1/t)/t^3)
could you show steps in working to sol.

I like x instead of t. You have
xy' = y/x + e^(1/x) / x^3
Change to the form
y' + yP(x) = Q(x)
y' + y*1/x^{2} = e^{1/x}/x^{4}
Now find the integrating factor
IF = exp(Int(P(x)) = exp(Int(1/x^{2})) = e^{1/x}
Now, y = 1/e^{1/x} Int(Q(x)*IF)
= e^{1/x} Int(e^{1/x}/x^{4} * e^{1/x} dx)
= e^{1/x}*(1/3x^{3} + C)
y = Ce^{1/x}  e^{1/x}/3x^{3}
Respond to this Question
Similar Questions

maths
find the general solution of the following first order differential equation. u(t): du/dt = u /t+2t pls show all working 
Mathematics
find the general solution of the following first order differential equation. dx/d(theta)=(xtan(theta))(cos(theta)) show working 
maths
please help find the general solution of the following first order differential equation. dx/dt = tx + 6t(exp)t^2 pls show working 
maths
find the general solution of the following first order differential equation. t*(dy/dt) = (y/t) + ((exp(1/t)/t^3) could you show steps in working to solution. 
mathematics
find the general solution of the following first order differential equation. u(t): du/dt =(u/(t+2t)) pls show all working 
maths
find the general solution of the following first order differential equation. dx/d(theta)=(xtan(theta))(cos(theta)) 
maths
find the general solution of the following first order differential equation. dx/dt = t*x + 6*t(exp)t^2 pls show working 
differential equations
Consider the 2nd order differential equation: x''(t)=xA(x^21)x'(t) x(0)= 0.5 x'0)= 0 ''= 2nd order,'= 1st order where A is a positive constant.As the value of A increases this equation becomes increasingly stiff. Convert this equation … 
maths
Solve the following 2nd order differential equation explicitly by expanding up to order x5, y''(x) = (1 + x^2)*y(x) pls show working y =f(x) 
maths
Solve the following 2nd order differential equation explicitly by expanding up to order x5, y''(x) = (1 + x^2)*y(x) pls show working y =f(x)